2020
DOI: 10.1016/j.ebiom.2020.102789
|View full text |Cite
|
Sign up to set email alerts
|

A glimpse into the eye of the COVID-19 cytokine storm

Abstract: The pathogenesis of pandemic coronavirus disease-2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) likely depends heavily on disruption of immune and inflammatory processes. Thus far, the precise immune mechanisms have not been fully elucidated or studied in detail. In this issue of EBioMedicine, Liu and colleagues [1] showed that patients with severe COVID-19 had lymphopenia and increased neutrophil counts along with high levels of circulating pro-inflammatory cytokines co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 8 publications
(8 reference statements)
1
52
0
Order By: Relevance
“…Studies performed on SARS-CoV suggested that AKI in SARS patients was the result of specific pathogenic conditions, such as the cytokine release syndrome [70], rather than active viral replication in the kidney. In consideration of the analogy between SARS-CoV and SARS-CoV-2, flow cytometry was used to study the immune phenotype and the function of peripheral blood mononuclear cells in COVID-19 patients [71]. Studies showed that patients infected by SARS-CoV-2 showed lymphopenia, mainly related to the significant reduction in absolute T cell counts, particularly cytotoxic T lymphocytes (CD8 + ), increased neutrophil counts and elevated levels of proinflammatory cytokines.…”
Section: Pathophysiology Of Kidney Damage Induced By Sars-cov-2mentioning
confidence: 99%
“…Studies performed on SARS-CoV suggested that AKI in SARS patients was the result of specific pathogenic conditions, such as the cytokine release syndrome [70], rather than active viral replication in the kidney. In consideration of the analogy between SARS-CoV and SARS-CoV-2, flow cytometry was used to study the immune phenotype and the function of peripheral blood mononuclear cells in COVID-19 patients [71]. Studies showed that patients infected by SARS-CoV-2 showed lymphopenia, mainly related to the significant reduction in absolute T cell counts, particularly cytotoxic T lymphocytes (CD8 + ), increased neutrophil counts and elevated levels of proinflammatory cytokines.…”
Section: Pathophysiology Of Kidney Damage Induced By Sars-cov-2mentioning
confidence: 99%
“…SARS-CoV-2 presents with increased proinflammatory cytokines and chemokines along with B-and T-cell depletion. In particular, the depletion of CD8+ T cells and increased levels of TNF-α, IL-6, and IL-10 are correlated with increased severity of COVID-19 [7]. It is also suggested that a possible rebound trigger could be induced by autoimmune response besides the detrimental effects of the virus in the organs and immune system stimulation when there is a delay between the complications and the initial symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…With acute viral overload, the immune response goes into overdrive, resulting in hyperinflammation, producing excessive cytokines. The “cytokine storm syndrome” is an important, consistent, and central theme in COVID-19 literature [ 13 , 78 , 79 ]. Understanding the mechanisms underlying the COVID-19-specific cytokine storm and targeting and quelling the hyperinflammatory response is necessary for the prevention of severe morbidity and death in the current COVID-19 pandemic, and also in any future viral outbreaks.…”
Section: Sars-cov-2 Infectivity Symptoms and Complicationsmentioning
confidence: 99%